Penerapan Pijat Akupresur pada Ibu Hamil Trimester I untuk Mengatasi Masalah Emesis Gravidarum di Wilayah Kerja Puskesmas Putri Ayu Kota Jambi - Rani Rizma Al Fatiha H; Sri Mulyani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Nausea and vomiting or emesis gravidarum are the most common discomforts in the first trimester of pregnancy. If nausea and vomiting are not treated immediately, the body will become weak, dehydrated and have a pale face. Based on the results of the study, Mrs. D, 32 years old, first trimester of pregnancy with the main complaint of nausea and vomiting. One way to reduce nausea and vomiting is with acupressure massage techniques. Acupressure massage is done by gently pressing the PC 6 point for 2 minutes, the aim of which is to have an effect on giving acupressure massage to pregnant women in the first trimester to overcome the problem of emesis gravidarum. The method used is a case study with data collection techniques through observation, interviews and physical examination with the superior intervention of acupressure massage to reduce emesis gravidarum or nausea and vomiting. The results showed that there was a diagnosis of nausea with the intervention of giving acupressure massage for 3 days. The results showed that after the acupressure massage there was a decrease in the Pregnancy Unique Quantification of Emesis and/or Nausea (PUQE) score on the first day of the intervention with a score of 8 (moderate nausea and vomiting category) after the day all three interventions with a score of 3 (mild nausea and vomiting category). Conclusion: Application of acupressure massage can reduce emesis gravidarum or nausea and vomiting in first trimester pregnant women.